Assessment of Oxidative Stress and Associated Biomarkers in Wild Avian Species - Siniša Faraguna; Suzana Milinković Tur; Sandra Sobočanec; Marija Pinterić; Maja Belić (Animals)
Reactive oxygen species (ROS) are natural by-products of cellular metabolism and are also formed in response to environmental stressors such as pollution, extreme temperatures, and ultraviolet radiation exposure. Physiological factors such as intense activity, growth, reproduction, nutrient deficiency, captivity, and disease also contribute to ROS production. While ROS, including free radicals, play a key role in cell physiology, including immune defense, their excessive accumulation can damage cellular components and cause oxidative stress when antioxidant defenses are overwhelmed. To regulate ROS levels, wild birds rely on enzymatic (e.g., catalase, superoxide dismutase, glutathione peroxidase) and non-enzymatic antioxidants (e.g., vitamins C and E, carotenoids). Oxidative stress affects important aspects of wild bird biology, including health, reproduction, and survival, and is closely linked to overall fitness. It is also linked to physiological challenges such as migration and the progression of various diseases affecting wild bird populations. The study of oxidative stress in wild birds requires the use of appropriate biomarkers to assess its role in disease development. A deeper understanding of the balance between ROS production and antioxidant defenses is essential to determine how wild birds cope with environmental and physiological challenges. In this review, we summarize the mechanisms of oxidative stress in wild birds and the role of antioxidants in maintaining health and promoting longevity in wild bird populations.